Time-resolved proteomic profile of Amblyomma americanum tick saliva during feeding. - Tae Kwon Kim; Lucas Tirloni; Antônio F M Pinto; Jolene K Diedrich; James J Moresco; John R Yates; Itabajara da Silva Vaz; Albert Mulenga (Public Library of Science (PLoS), 2020)
Amblyomma americanum ticks transmit more than a third of human tick-borne disease (TBD) agents in the United States. Tick saliva proteins are critical to success of ticks as vectors of TBD agents, and thus might serve as targets in tick antigen-based vaccines to prevent TBD infections. We describe a systems biology approach to identify, by LC-MS/MS, saliva proteins (tick = 1182, rabbit = 335) that A. americanum ticks likely inject into the host every 24 h during the first 8 days of feeding, and towards the end of feeding. Searching against entries in GenBank grouped tick and rabbit proteins into 27 and 25 functional categories. Aside from housekeeping-like proteins, majority of tick saliva proteins belong to the tick-specific (no homology to non-tick organisms: 32%), protease inhibitors (13%), proteases (8%), glycine-rich proteins (6%) and lipocalins (4%) categories. Global secretion dynamics analysis suggests that majority (74%) of proteins in this study are associated with regulating initial tick feeding functions and transmission of pathogens as they are secreted within 24-48 h of tick attachment. Comparative analysis of the A. americanum tick saliva proteome to five other tick saliva proteomes identified 284 conserved tick saliva proteins: we speculate that these regulate critical tick feeding functions and might serve as tick vaccine antigens. We discuss our findings in the context of understanding A. americanum tick feeding physiology as a means through which we can find effective targets for a vaccine against tick feeding.